Contemporary Czech Morphology and its Developmental Dynamics - Uličný, Oldřich (Bohemica Olomucensia, 2017)
A certain shift to the deflectivation enforces in the morphological structure of the contemporary Czech language. At the same time, tendencies to turn towards the analytic language construct are registred. This phenomenon, which has already begun in the older phases of development, is currently increasing in intensity and scope. In this paper, four main types of deflectivation in contemporary Czech are presented, which are documented by numerous references to the behavior of nouns, adjectives, pronouns and verbs.
Keywords: development of language; morphology; inflection; typology of languages; fusional languages; analytic languages